Irinotecan Plus Doxorubicin Hydrochloride Liposomes for Relapsed or Refractory Wilms Tumor - Wang, Juan; Zhang, Lian; Guo, Lanying; Que, Yi; Zhang, Yu; Sun, Feifei; Zhu, Jia; Lu, Suying; Huang, Junting; Wu, Liuhong; Cai, Ruiqing; Zhen, Zijun; et al. (Frontiers in Oncology, 2021)
Purpose: The prognosis of relapsed or refractory pediatric Wilms tumor (WT) is dismal, and new salvage therapies are needed. This study aimed to evaluate the efficacy of the combination of irinotecan and a doxorubicin hydrochloride liposome regimen for relapsed or refractory pediatric WT. Patient and methods: The present study enrolled relapsed or refractory pediatric WT patients who were treated with the AI regimen (doxorubicin hydrochloride liposomes: 40 mg/m2 per day, d1 and irinotecan: 50 mg/m2 per day with 90-min infusion, d1-5; this regimen was repeated every 3 weeks) at Sun Yat-sen University Cancer Center from July 2018 to September 2020. Response was defined as the best-observed response after the last two cycles according to the Response Evaluation Criteria of Solid Tumors (RECIST 1.1), and toxicity was evaluated according to the Common Terminology Criteria for Adverse Events (CTCAE 4.03). Result: A total of 16 patients (male: female, 8:8) with a median age of 4.2 years (0.5 to 11 years) with relapsed or refractory disease were enrolled in this study, including 14 patients with relapsed disease and 2 patients with refractory disease. These patients received 1 to 8 courses (median 3 courses) of the AI regimen. Fourteen patients were assessable for response: 2 complete response (CR), 5 partial response (PR), 2 stable disease (SD), and 5 progressive disease(PD). The objective response rate was 50% (2 CR, 5 PR), and the disease control rate was 64% (2 CR, 5 PR, and 2 SD). Seven out of 14 patients (50%) were alive at the last follow-up, ranging from 2.6 to 32.4 months. The median progression-free survival and median overall survival were 3.5 months (range 0.5-12 months) and 8 months (range 1-28 months), respectively. Sixteen patients were assessable for toxicity, with the most common grade 3 or 4 adverse events being alopecia (62%), leucopenia (40%), abdominal pain (38%), diarrhea (23%), and mucositis (16%), etc. No fatal adverse events have been observed, and modest adverse effects can be administered. Conclusion: Irinotecan and doxorubicin hydrochloride liposome regimens have positive efficacy on relapsed or refractory pediatric WT with well-tolerated toxicity. A prospective clinical trial is warranted.